ANALISIS KELAYAKAN BISNIS DAN EFISIENSI PRODUKSI PABRIK TAHU TRI LESTARI DI KOTA JAMBI - Dyah Najla Kushartiwi; Eja Armaz Hardi (ICONS: Islamic Economics Journal, 2025)
This study aims to analyze the business feasibility and production efficiency of Tri Lestari Tofu Factory in Jambi City. The method used in this research is descriptive qualitative with a case study approach. Data were collected through direct observation, in-depth interviews with factory owners and employees, and documentation of the production process. The results showed that the tofu production process at Tri Lestari Factory has been sustainable with manual and semi-mechanized systems, but there are still opportunities to improve efficiency, especially in energy use and raw material management. Tofu waste management is carried out by utilizing solid waste as animal feed and liquid waste is drained into open channels, although it does not meet environmentally friendly waste treatment standards. From a sustainability perspective, the factory has implemented circular economy principles in a simple way, but there is a need to increase awareness and technology in waste management so that negative impacts on the environment can be minimized. Therefore, education, training, and appropriate technological support are needed so that the factory can improve its production efficiency while preserving the surrounding environment.